Symmetrical comparison of crown size, morphology and gingival shape in maxillary incisors - Ghimire, Barsha; Dhital, Shaishab (Journal of Kathmandu Medical College, 2022)
Background: Maxillary anterior tooth proportion has special value in dental aesthetics. Restorative dentistry often involves correcting tooth size discrepancies. Therefore, dental biometrics should play an important role in the planning of an aesthetic restoration. Objectives: To assess and compare clinical crown dimensions and classify crown shape and gingival shape of the maxillary incisors in order to collect anatomical data on the anterior teeth of young population visiting the tertiary centre. Methods: This descriptive cross-sectional study conducted in department of Prosthodontics in November 2021 after getting ethical approval among dental students and patients attending the hospital, with permanent healthy dentitions. Impression of maxillary and mandibular arches were made with alginate and poured in dental stone. Measurement of maxillary central incisors was done for length and thickness with the digital vernier calliper. Convenience sampling was done. Data were recorded and analysis done with SPSS v.20. Results: The mean value of crown length, crown thickness, mesiodistal width of left central incisor was greater compared to the right side (Left vs Right: 9.01 ± 1.14 mm vs 9 ± 1.14 mm , 7.04 ± 0.67 mm vs 6.96 ± 0.61 mm, 8.25 ± 0.59 mm vs 8.20 ± 0.51 mm). Conclusion: Crown length and crown width of maxillary left central incisor were greater compared to maxillary right central incisor. Shape of maxillary incisors determines the shape of the gingiva. The average values of length and widths of the central incisors derived from this study can be a valuable template for prosthodontic and aesthetic planning.